Connected Metaballs of a Ptpd/C Binary Alloy as a Nanocatalyst for Oxygen Reduction in Proton-Exchange-Membrane Fuel Cells - Herrera-Diaz, F; Herrera-Diaz, F (American Chemical Society, 2025)
This study investigates the development of a nanostructured connected metaball (CMB) PtPd/C binary alloy electrocatalyst for the improved oxygen reduction reaction (ORR) performance in polymer electrolyte membrane fuel cells (PEMFCs). The catalyst was synthesized using a modified molten-salt method and characterized through various physical and electrochemical techniques. X-ray diffraction (XRD) and transmission electron microscopy (TEM) confirmed the formation of connected metaballs of a PtPd alloy structure with an similar to 8 nm metaball size. Electrochemical testing revealed that the CMB PtPd/C electrocatalyst exhibited 10 times enhanced mass (I m) activity and 5 times specific (I s) activity than Pt/C, respectively. The enhanced performance is attributed to the connected spheres of PtPd alloys and synergistic effects among the constituent elements. Notably, the nanostructured CMB network catalyst demonstrated excellent stability, maintaining high activity for up to 60,000 potential cycles before the gradual decline. CO stripping voltammetry indicated a positive shift in the CO oxidation onset potential, correlating with the improved ORR activity. The results suggest that connected metaballs of the PtPd/C system create a more active and durable ORR catalyst. This geometry approach offers a promising direction for developing high-performance, low-platinum content catalysts for PEMFC applications.